Vulvar Merkel Carcinoma: A Case Report - C. Iavazzo; M. Terzi; P. Arapantoni-Dadioti; V. Dertimas; G. Vorgias (Case Reports in Medicine)
This is a new case of Merkel cell carcinoma of the vulva. It is a rare neuroendocrine carcinoma with an aggressive behavior. Because of its rarity in this location, it is not clear whether it behaves differently from the usual neuroendocrine carcinomas of the skin. A case of a 63-year-old patient with vulvar Merkel carcinoma is presented. The clinical presentation, microscopic and immunohistochemical features, and treatment are discussed.